2013 Universiade match analysis from the perspective of wrestling's new rules - Türkmen, M.; Imamoglu, O.; Demirhan, B. (International Journal of Wrestling Science, 2013)
OBJECTIVE: In this study, the dynamism of the new rules brought to wrestling was investigated by making technical analysis of the 2013 Universiade Games in men`s Greco-Roman and freestyle wrestling contests. METHODS: Wrestling competitions winning ways, the scores obtained according to the circuits, points types and the duration of competitions; were investigated from 133 Greco-Roman and 197 freestyle competitions. RESULTS: From freestyle and Greco-Roman 2013 Universiade games wrestling competitions, in Greco-Roman style, the number and victory are as 45.5% and technical victory is as 42.5% with 7 points difference. In Freestyle, victory by points was observed in 39.7% of the matches, and technical victory in 50.9% (with 7 points difference). Victory by Touché was very low. According to the form of victories there was no significant difference in Greco-Roman and freestyle competitions (p> 0.05). In elimination and 3rd and 5th matches technical victory was obtained with maximal 7 points more frequently than victory by point. The points scored inthe first circuit (round) of each match in freestyle was 6.14, while in Greco-Roman style it was 5.26. The points obtained in the second round of each match in freestyle were as 2.78, while in Greco-Roman style it was 3.12. The total points obtained by the victors in Freestyle for each match was 7.44 and the points obtained by the losers are 1.89. According to styles there is significant difference in one and two-point match numbers (p <0.05). In Greco-Roman style one-point matches were observed more than in freestyle, and in freestyle two-point matches were observed more than in Greco-Roman style. According to the styles there was no difference in 3 and 5 point scores (p> 0.05). Greco-Roman style competitions lasted 3.96 minutes, while the freestyle competitions lasted 3.74 minutes on average. The matches lasting 6 minutes were 58 in Greco-Roman style and 72 matches in Freestyle. CONCLUSION: According to the new rules, wrestling matches were seen to average less than 4 minutes in duration. We can say that either taking more points per minute, along with the shortened duration of the matches by technical superiority brought vitality and dynamism to wrestling and increased the enjoyment of watching. In this context it was observed that FILA reached its purpose practically by the idea of bringing dynamism and vitality to wrestling with new rules.